2022
DOI: 10.1007/s40820-022-00841-5
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Oxidation-Induced Phase Engineering for MOFs Derivatives Via Spatial Confinement Strategy Toward Enhanced Microwave Absorption

Abstract: Precisely reducing the size of metal-organic frameworks (MOFs) derivatives is an effective strategy to manipulate their phase engineering owing to size-dependent oxidation; however, the underlying relationship between the size of derivatives and phase engineering has not been clarified so far. Herein, a spatial confined growth strategy is proposed to encapsulate small-size MOFs derivatives into hollow carbon nanocages. It realizes that the hollow cavity shows a significant spatial confinement effect on the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(43 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…Eventually, the Co/C@CNF aerogel reached an EMI SE of around 35.1 dB at a density of 1.74 mg•cm −3 , and the corresponding SSE was 20,172.4 dB•cm 3 •g −1 . Wang et al also reported the enhancement in EMI SE of CNF/MXene aerogels (CTA) with aligned porous structure [120]. After annealing, anisotropic morphology could be well preserved (Fig.…”
Section: Porous Architectures With Biomimetic Ordered Pores For High-...mentioning
confidence: 83%
“…Eventually, the Co/C@CNF aerogel reached an EMI SE of around 35.1 dB at a density of 1.74 mg•cm −3 , and the corresponding SSE was 20,172.4 dB•cm 3 •g −1 . Wang et al also reported the enhancement in EMI SE of CNF/MXene aerogels (CTA) with aligned porous structure [120]. After annealing, anisotropic morphology could be well preserved (Fig.…”
Section: Porous Architectures With Biomimetic Ordered Pores For High-...mentioning
confidence: 83%
“…Due to the high conductivity, the impedance mismatch at the interfaces between fiber and air leads to strong reflection of EM waves (Figure S24). Meanwhile, a large induced current is generated inside the fibers because of the high conductivity, which can significantly convert EM energy into thermal energy. , Besides, polarization relaxation loss and magnetic loss also contribute to the attenuation of EM waves inside the fibers. Figure S25 presents the frequency dependence of the complex permittivity (ε r = ε′ – i ε″) and complex permeability (μ r = μ′ – i μ″) of the M 0.1 LM 5 S textile. The presence of resonant peak in the imaginary permittivity (ε″) curve and the Cole–Cole semicircles in ε″−ε′ curve demonstrate the generation of polarization relaxation loss (Figure S25a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Set the fully open boundary condition and selected the monitoring frequency of 14 GHz. The incident angle of the electromagnetic wave was adjusted (‐60°‐60°), and the value was calculated by S (the area of the simulation model), λ (electromagnetic wave wavelength), E s (the electric field intensity), and E i (the incident wave): [ 64 ] RSC(dB m2)badbreak=10logfalse(false(4πS/λ2false)|ES/Enormali|false)2\[ \begin{array}{*{20}{c}}{RSC\left( {dB\,{m^2}} \right) = 10\log {{\left( {\left( {4\pi S/{\lambda ^2}} \right)|{E_S}/{E_{\rm{i}}}|} \right)}^2}}\end{array} \] …”
Section: Methodsmentioning
confidence: 99%
“…Set the fully open boundary condition and selected the monitoring frequency of 14 GHz. The incident angle of the electromagnetic wave was adjusted (−60°-60°), and the value was calculated by S (the area of the simulation model), λ (electromagnetic wave wavelength), E s (the electric field intensity), and E i (the incident wave): [64] RSC dBm S E E S π λ ( )…”
Section: Methodsmentioning
confidence: 99%